Assessing the Prevalence of Incidental Findings Identified by CTPA in Women of Reproductive Age - Champion, Nigel; Hogan, Sarah; Flemming, Jeffery (Emergency Medicine International, 2018)
Background and Objective. Though multiple studies have evaluated the prevalence of incidental findings identified by CTPA, none have done so with a focus on reproductive-age females with normal chest X-ray (CXR). Due to a comparatively lower breast radiation dose, the oft-recommended alternative to CTPA in this patient group is a V/Q scan. However, these are limited in their assessment of these alternate findings; therefore, it is of particular importance to evaluate the likelihood of these findings on CT in this patient group, which is the goal of this study. Methods. Through a review of our PACS system, female patients aged 18-50 years who underwent diagnostic CTPA prior to April 1, 2017, were identified. The 100 most recent cases which had a normal CXR within 48 hours of CTPA were included. Incidental/non-PE findings were then divided into PE-positive (PE+) and PE-negative (PE-), and subcategorized into types I, II, III, and nil non-PE finding groups. Type I findings required immediate follow-up or intervention, type II findings required outpatient follow-up, and type III findings required no follow-up or were previously known. Results. PE was detected in 15% of scans. Type I findings were found in 8% of patients (0% of PE+, 9.4% of PE-), type II findings in 10% of patients (13.3% of PE+, 9.4% of PE-), type III findings in 34% of patients (40% of PE+, 32.9% of PE-), and nil non-PE finding in 48% of patients (46.7% PE+, 48.2% of PE-). Conclusion. While CTPA identifies incidental findings in the majority of patients, a small minority of these findings are likely to alter immediate management. In the context in increased radiation risk, this strengthens the argument that alternate imaging modalities such as V/Q should be strongly considered for the investigation of potential PE in women of reproductive age with normal CXR.